The impact of a cervical dysplasia diagnosis on individual cancer prevention habits over time: a bicentric case-control study - Rippinger, Nathalie; Heinzler, Julia; Bruckner, Thomas; Brucker, Janina; Dinkic, Christine; Rom, Joachim; Sohn, Christof; Schott, Sarah (Archives of gynecology and obstetrics, 2019)
PurposeAnnual cervical cancer screening is recommended in Germany as a part of the statutory preventive care. Abnormal results can provoke psychological distress and anxiety, compromising women’s adherence. Little is known about how a cervical dysplasia impacts adherence follow-up visits and prevention habits over time. To optimize care strategies, this study aims to identify women at risk for nonadherence to follow-up visits after a screening event.MethodsBetween November 2015 and May 2017, participants with an abnormal Pap smear at the Heidelberg and Leipzig University Hospitals received a four-part questionnaire (sociodemographic data, PHQ-D, self-designed fear and prevention habit questions) at the first consultation (T1) and subsequently after 3 (T2) and 6 (T3) months; healthy controls completed the questionnaire at T1.Results132 women with an abnormal Pap smear [with conization: S1 (n = 68, 51.5%), without intervention: S2 (n = 64, 48.5%)] and healthy controls (K, n = 101) generally adhered to gynecological checkups, except S1 6 months after the first diagnosis (S1/T3 − 0.47, signed rank p < 0.0005). Knowledge of primary prevention information, i.e., HPV vaccination, was significantly higher among K (K 58%, S1 29%, S2 44%, Chi-squared p = 0.01) as was vaccine uptake (K 39% versus S1/S2 7% and 17%, respectively, Chi-squared p = 0.0004). Fear of upcoming Pap smears rose significantly over time (S1/T1-S1/T2-S1/T3, Wilcoxon signed-rank test p < 0.001) and was higher among those with conization at T2 (Chi-square test, p = 0.01) and partially accompanied by panic disorders at T1 (Chi-square test p = 0.035). Realization of general preventive habits rose significantly among women without an operative procedure (S2) over the study.ConclusionThis study advances the understanding of non-participation in follow-up visits after a dysplasia diagnosis, identifying post-conization women as a special risk group for decreased adherence.
Gesehen am 01.04.2019